A New Isoflavonoid from the Rhizomes of Cyperus rotundus - Cheng, Cai-Hong; Chen, Yi-Rong; Ye, Qing-Qing; Liang, Yan; He, Xiao-Rong; Zhou, Zhong-Liu; Feng, Zong-Cai (Asian Journal of Chemistry, 2014)
A new isoflavonoid, 5,7,4'-trihydroxy-2'-methoxy-3'-prenylisoflavone (1), along with eleven phenolic compounds (2-12), licoricone (2), 6-O-p-hydroxybenzoyl-6-epi-aucubin (3), 6-O-p-hydroxybenzoyl-6-epi-monomelittoside (4), 7-O-p-hydroxybenzoyl-8-epi-loganic acid (5), verproside (6), syringopicroside B (7), syringopicroside C (8), oleuropeinic acid (9), oleuroside (10), 10-hydroxyoleuropein (11), senburisideI (12), were obtained from the rhizomes of Cyperus rotundus. Their chemical structures were elucidated on the basis of UV, IR, MS, NMR spectroscopic analyses. Compound 12 showed considerable macrophages respiratory burst (MRB) inhibitory activity in the test with IC50 value of approximately 27 μM.